Predicting disasters and protecting rights - Ginnetti, J; Schrepfer, N (Refugee Studies Centre, University of Oxford, 2012)
In order to prevent or reduce disaster-related displacement, we need to address some clear gaps in both knowledge and capacity by improving research on and awareness of disaster risks and associated human rights, and the capacity to address them.